(untitled) (Confluenţe Bibliologice, 2017)
This article is devoted to the symbol of library in two books from a cycle of novels „The Secret Zoo” by Bryan Chick („Children’s Crown Award” in 2016). The symbol is connected with problems of space design and social mission of library in 21-th century.